Merdeka Curriculum Innovation in Building Students Independent Learning Character in Mathematics Subjects at The Primary Schools - Prayitno, Harun Joko; Oktafiani, Anis (International Conference on Education for All, 2024)
This research aims to implement the Merdeka Curriculum innovation, focusing on fostering students independent learning characteristics in the context of mathematics subjects at the elementary school level, using the Classroom Action Research (CAR) method. The Merdeka Curriculum emphasizes students freedom in learning, encouraging independence and a deeper understanding of mathematical concepts. The research was conducted using the CAR method with four main stages, following the Miles and Huberman model, which employs a comprehensive and intertwined analysis approach. The activities in this data analysis include 1) Data collection; 2) Data reduction; 3) Preliminary presentation/display of data; and 4) Drawing conclusions. The research results indicate an improvement in students independent learning characteristics in mathematics subjects through the Merdeka Curriculum innovation. There is increased active involvement of students in learning, with a higher level of independence demonstrated in solving mathematical problems. Teachers play a crucial role in delivering materials in an engaging manner, utilizing learning media, and providing individual support to students. Despite significant progress, some obstacles remain, such as varying levels of understanding among students. Therefore, this research recommends continuous reflection and adjustments in implementing the Merdeka Curriculum to enhance students independent learning characteristics sustainably. The implementation of P5 innovation in the Merdeka Curriculum can positively contribute to developing students independent learning characteristics in elementary school.